UJI EFEKTIVITAS EKSTRAK BUAH PARIJOTO (Medinilla speciosa Blume) TERHADAP PERBAIKAN HISTOPATOLOGI PERLEMAKAN HATI PADA MENCIT JANTAN (Mus musculus L) GALUR BALB/C MODEL HIPERLIPIDEMIA - Inasa Nabila (2022)
Background: Fatty liver is a liver condition that has a fat content of more than 5% of the total weight of the normal liver in people who rarely or do not have the habit of drinking alcohol. Hyperlipidemia is a risk factor for fatty liver. Parijoto fruit is thought to be able to prevent the occurrence of fatty liver. This study aims to determine the effectiveness of parijoto fruit extract in improving the degree of fatty liver in male mice with Balb/c strain hyperlipidemia model. Methods: A total of 30 male mice (Mus musculus L) Balb/c strain aged 8 weeks weighing 20-30 grams were randomly assigned to 6 groups, namely the control group on standard feed (K0), simvastatin control (K+), control high-fat diet and cholesterol (K-), parijoto fruit extract treatment at a dose of 5.6 mg/20grBW/day (P1), parijoto fruit extract treatment at a dose of 8.4 mg/20grBW/day (P2), and parijoto fruit extract treatment at a dose of 11.2 mg/20grBW/day (P3). Results: Analysis of histopathological data on fatty liver using the Kruskal-Wallis test followed by the Mann-Whitney test. The results of the Kruskal-Wallis test found a significant difference in the improvement in the degree of steatosis in each group (p=0.021). Histopathological analysis showed that the parijoto fruit extract at a dose of 5.6mg/20grBW/day increased the response to improvement in the degree of steatosis compared to mice given PTLK (p>0.05). Parijoto fruit extract doses of 8.4 and 11.2 mg/20gBW did not increase the response to improvement in the degree of steatosis on histopathological features of fatty liver (p>0.05). Conclusion: Parijoto fruit extract improved the degree of steatosis on the histopathological feature of fatty liver in male Balb/c mice. This shows that parijoto fruit extract can be used as an alternative hepatoprotector therapy.